Effects of Stigeoclonium nanum, a freshwater periphytic microalga on water quality in a small‐scale recirculating aquaculture system. (30th August 2018) - Mohamed Ramli, Norulhuda; Yusoff, Fatimah M.; Giatsis, Christos; Tan, Geok Yuan A.; Verreth, Johan A. J.; Verdegem, Marc C. J.
Abstract: Recirculating aquaculture systems (RAS) are becoming important for aquaculture due to land and water supply limitations and due to their low environmental impact. Bacteria are important in RAS as their role in nutrient recycling has been the main mechanism for waste removal in these systems. Besides bacteria, the presence of microalgae can benefit the water quality through the absorption of inorganic nitrogen (ammonium and nitrate) and phosphorus from the water. However, reports on the inclusion of microalgae in RAS are very scarce. The objective of this study was to determine the effect of microalgae on water quality (total ammonia nitrogen, nitrite, nitrate and phosphate) and bacterial composition in a freshwater small‐scale RAS. A periphytic microalga, Stigeoclonium nanum, was used in this study. A rapid fingerprint analysis, denaturing gradient gel electrophoresis (DGGE), was used to determine the bacterial community composition in the water. The results showed that ammonia concentrations were not significantly different ( p > 0.05) between RAS with microalgae (RAS+A) and RAS without microalgae (RAS‐A). However, nitrite, nitrate and phosphate were significantly lower in the RAS+A than the RAS‐A ( p < 0.05). Pielou's evenness and Shannon diversity index of bacterial community between the treatments were not different ( p > 0.05); however, the bacterial composition between the treatments was significantly different ( p < 0.05).